The role of transcatheter mitral valve therapy in heart failure. (20th May 2019) - Treede, Hendrik; Charitos, Efstratios I
Summary: Mitral valve regurgitation is detected in up to 75% of patients with heart failure. Interventional mitral valve therapies can be used to treat mitral regurgitation with very low morbidity and mortality rates and minimal invasiveness. Devices intended for the replacement of the mitral valve still require significant development and refinement before entering clinical practice on a large scale. The derived benefit of these therapies, the priority (repair over replacement) and the therapeutic role in patients with secondary mitral regurgitation due to heart failure remain to be investigated.